2007
DOI: 10.1002/ange.200702885
|View full text |Cite
|
Sign up to set email alerts
|

Highly Birefringent Materials Designed Using Coordination Polymer Synthetic Methodology

Abstract: Sehen Sie doppelt?! Die Kombination des hoch anisotropen Terpyridinliganden mit dem anisotropen linearen Dicyanoaurat‐Ion führt zu einer Reihe von Koordinationspolymeren, die zu den Festkörpern mit der stärksten Doppelbrechung überhaupt zählen (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…For example, Pb‐based coordination polymers containing various terpy, terpy analogues and 2,2′‐bipyridine (bipy) ligands have been reported that possess similar structural features and have axial substituents of N‐cyano‐bonded [Au(CN) 2 ] – units rather than halides. Specifically, Pb(terpy)[Au(CN) 2 ] 2 and Pb(Cl‐terpy)[Au(CN) 2 ] 2 are seven‐coordinate Pb II structures containing one capping ligand, two axial and two equatorial N‐cyano ligands in which the equatorial bond lengths are elongated, which suggests that the lone pair exists opposite the central Pb–Py bond , , . Pb(bipy) 2 [Au(CN) 2 ] 2 is eight‐coordinate and has a different structure type but also contains elongated N‐cyano bonds trans to the Pb–Py bonds, indicative of a stereoactive lone pair in this coordination site .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pb‐based coordination polymers containing various terpy, terpy analogues and 2,2′‐bipyridine (bipy) ligands have been reported that possess similar structural features and have axial substituents of N‐cyano‐bonded [Au(CN) 2 ] – units rather than halides. Specifically, Pb(terpy)[Au(CN) 2 ] 2 and Pb(Cl‐terpy)[Au(CN) 2 ] 2 are seven‐coordinate Pb II structures containing one capping ligand, two axial and two equatorial N‐cyano ligands in which the equatorial bond lengths are elongated, which suggests that the lone pair exists opposite the central Pb–Py bond , , . Pb(bipy) 2 [Au(CN) 2 ] 2 is eight‐coordinate and has a different structure type but also contains elongated N‐cyano bonds trans to the Pb–Py bonds, indicative of a stereoactive lone pair in this coordination site .…”
Section: Resultsmentioning
confidence: 99%
“…The targeted series of Pb II complexes feature the tridentate 2,6‐bis(benzimidazol‐2‐yl)pyridine ligand (bbp); the Pb II /bbp combination is of particular interest, because previous reports have shown that non‐Pb II ‐based bbp materials and Pb II systems with other planar aromatic capping ligands, can be highly birefringent by virtue of aligning the highly polarizable anisotropic components. Thus, a merging of these two components in the quest for highly birefringent coordination polymer materials is a logical progression.…”
Section: Introductionmentioning
confidence: 99%
“…The trends observed in ical shift anisotropy can be correlated with lone-pair activity. More recently, a related series of [PbA C H T U N G T R E N N U N G (X-terpy){Au(CN) 2 } 2 ] (X = H, 4'-chloro and 4'-bromo; terpy = 2,2';6',2''-terpyridine) coordination polymers exhibiting extremely high bi-A C H T U N G T R E N N U N G refringence was reported, [5,7] but the stereochemical activity of their lone pair was not spectroscopically examined. A pair of related dicyanamide-containing (DCA, [N(CN) 2 ] À ) coordination polymers has also been prepared for comparison.…”
mentioning
confidence: 97%
“…ADF calculations predict that d iso = À2027 ppm, W = 2307 ppm and k = À0.16, exhibiting the largest calculated span for the terpyridine-containing co- (6), showing an isomorphous structure to 3. [7] (For a colour image see Figure S15 in the Supporting Information) ordination polymers. The calculated NMR parameters are similar to those of 3 with an identical chemical shift tensor orientation ( Figure S6 in the Supporting Information), suggesting that a similar NMR spectrum might be observed, a not unexpected result, however, given the structural homology between 3 and 6.…”
mentioning
confidence: 99%
See 1 more Smart Citation